Monogenic Obesity in Children: Current Perspectives and Clinical Implications - Cristianne Confessor Castilho Lopes; Vitor Ohana Marques Azzini; Natascha Szumsztajn Beker; Eduardo Barbosa Lopes; Lucas Castilho Lopes; Maria Eduarda Castilho Lopes; Fábio Herget Pitanga; Larissa Silva Guimarães (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Monogenic obesity is characterized by a mutation in a single gene, which directly influences metabolism, appetite control or other biological pathways associated with body weight regulation. Objective: To provide practical insights for healthcare professionals working with affected children to improve health outcomes and quality of life. Methods: This study constitutes a systematic review, classified as exploratory and descriptive. The preparation of the research was a bibliographical search in electronic databases on methods associated with RSL (Systematic Literature Review) and the applications of SMARTER (Simple Multi-Attribute Rating Technique using Exploiting Rankings). Results: A comprehensive systematic search of the literature yielded a total of 4125 articles referring to the incidence of obesity and overweight in adolescents, of which 20 articles were eligible to be included in this systematic review. Conclusion: With a continued and coordinated effort, it is possible to significantly improve health outcomes for these children, preparing them for a brighter future.